The Impact of Social Responsibility Practices on The Financial Performance of Listed Banks in The Damascus Securities Exchange 2009-2023 (Journal of Hama University, 2025)
The Research Aimed To Measure The Impact of Social Responsibility Practices on Financial Performance Measured by Return on Equity, Liquidity Ratio and Capital Adequacy Ratio for The Saudi French Bank and The Bank of Syria and Overseas During The Period From 2009 to 2023 AD, AS The Research Relied on Simple Regression Models Using The Statistical Package for Social Sciences (SPSS, V.25) to Analyze The Data.The Results Showed a Direct Effect of Social Responsibility Practices on Financial Performance Measured by Return on Equity and Liquidity Ratio for The Saudi French Bank and The Bank of Syria and Overseas. The Results Also Showed No Effect of Social Responsibility Practices on Financial Performance Measured by Capital Adequacy Ratio for The Banks Studied.
Keywords: Keywords: Financial Performance, Social Responsibility, Return on Equity, Liquidity Ratio, Capital Adequacy Ratio.